Phytochemical screening and antioxidant evaluation of millet varieties of Pakistan - Naz, Nosheen (Array, 2020)
The current research was planned to measure the comparative phytochemical and anti-oxidative potential of aqueous and methanolic extracts of two indigenously grown millet varieties of Pakistan. The locally available millet varieties, i.e. MB-87 and AF-POP flours were chemically characterized through the proximate and mineral analysis. The antioxidant extract was prepared in water and methanol. The extracts were screened for saponins, terpenoids, flavonoids and tannins; methanolic extract of MB-87 and AF-POP showed flavonoids in an average quantity (++), whilst aqueous extract had only trace (+) values. The phytochemical screening showed the presence of saponins only in the aqueous extract of both varieties. However, terpenoids and tannins were present in both methanolic and aqueous extracts. During antioxidant evaluation, millet methanolic extracts showed higher level of TPC and DPPH of MB-87 and AF-POP as 0.30±0.001 & 0.23±0.0012 mg GAE/g and 48±0.96 &46±1.09%, respectively. However, the β-carotene activity of the aqueous extract of both varieties (MB-87 and AF-POP) was recorded higher. In a nutshell, the methanolic extract of MB-87 has an appreciable atioxidant profile. Furher research should be planned to screen the important constituents of Pakistani millet varieties.